Gelfand pair associated with a Hoph algebra and a coideal - Chapovsky, Yu. (Український математичний журнал, 1994)
A pair of a compact quantum group and a coideal in its dual Hopf *-algebra is considered. A notion of a Gelfand pair and a strict Gelfand pair is introduced. For a strict Gelfand pair, two hypercomplex systems dual to each other are constructed. As an example, the quantum analog of the pair (U(n), SO(n)) is considered. Розглянуто пару компактної квантової групи і коідеал у її дуальній Хопф-алгебрі. Вводиться поняття пари Гельфанда і строгої пари Гельфанда. Для строгої пари Гельфанда побудовано дві гіперкомплексні системи, які є дуальні одина до одної. Як приклад розглянуто квантовий аналог пари (U(n), SO(n)).